(untitled) (History Journal «Jerónimo Zurita», 2023)
This paper pretends to understand the escape and the Pyrenean border crossing during the “Retirada” into France after the ending of the Spanish Civil War as a shared traumatic experience for the memory of the republican exile in 1939. Based on the common experience that has shaped a collective memory, the main objective in this paper is to analyze the different phases of the retreat through the personal remembrances and how the border crossing has been interpreted by those memories. A use of the exile’s first stage from a private point of view that has succeeding in leaving a mark in the public space through the activities of some museological initiatives.